High Resolution 3D Optical Scanning of Crossties to Assess Cross-Sectional Parameters and the Effects of Long-Term Abrasion and Wear - Beck, B. Terry; Robertson, Aaron A.; Peterman, Robert J.; Riding, Kyle A. (Rural Railroad Safety Center, Kansas State University., 2021)
This report documents measurement of the 3D geometrical properties associated with prestressed concrete railroad ties that have been subject to long-term in-track loading. A commercially-available 3D laser-based optical scanning system was used to scan the surface of sampled in-service crossties to a spatial resolution of about 1-mm, resulting in a 3D solid body CAD model of each scanned tie. A high-speed algorithm was developed to process the detailed cross-section geometrical parameters to an axial resolution of 0.5 inches, achieving an overall processing time of only a few minutes. The agreement between the ideal CAD model cross-section parameters and the measured (scanned) parameters was found to be excellent. Measured crosstie cross-sectional parameters used in support of on-going FRA project work included cross-sectional area, area moment of inertia, neutral axis position, eccentricity, and shape factor.
Keywords: Prestressed Concrete; Railroad Ties; Crossties; 3D Optical Scanning; Geometry; Shape Factor